2010
DOI: 10.1128/jb.00255-10
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Basis of Laboratory Adaptation in Caulobacter crescentus

Abstract: The dimorphic bacterium Caulobacter crescentus has evolved marked phenotypic changes during its 50-year history of culture in the laboratory environment, providing an excellent system for the study of natural selection and phenotypic microevolution in prokaryotes. Combining whole-genome sequencing with classical molecular genetic tools, we have comprehensively mapped a set of polymorphisms underlying multiple derived phenotypes, several of which arose independently in separate strain lineages. The genetic basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
185
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(190 citation statements)
references
References 41 publications
2
185
0
3
Order By: Relevance
“…1) that implement biogenesis of polar organelles, replication and segregation of the chromosome, and cytokinesis (1)(2)(3)(4). The circular 4-Mb genome has 3,885 ORFs and 199 noncoding RNAs (5,6). mRNA profiling by microarrays or RNA-seq (7)(8)(9)(10) and global promoter activity profiles from 5′ Global RACE experiments (11) have shown that several hundred Caulobacter mRNAs have significant temporal transcriptional variation over the cell cycle.…”
mentioning
confidence: 99%
“…1) that implement biogenesis of polar organelles, replication and segregation of the chromosome, and cytokinesis (1)(2)(3)(4). The circular 4-Mb genome has 3,885 ORFs and 199 noncoding RNAs (5,6). mRNA profiling by microarrays or RNA-seq (7)(8)(9)(10) and global promoter activity profiles from 5′ Global RACE experiments (11) have shown that several hundred Caulobacter mRNAs have significant temporal transcriptional variation over the cell cycle.…”
mentioning
confidence: 99%
“…The CB15N WT C. crescentus strain, used in this study, is a strain that adapted to laboratory growth conditions and lost its ability to attach to surfaces. For more information on this strain, see (36).…”
Section: Experimental Procedures Bacterial Strains Media and Plasmidsmentioning
confidence: 99%
“…The presence of these genes could alter the capsular properties of C. crescentus, and as a consequence interfere with phage ΦCr30 attachment to the S-layer. Moreover, the presence of a modified capsule on the cell surface might affect the cell density and hydrodynamic properties, which in turn would be responsible for the change in the sedimentation properties (127).…”
Section: Regulation Of Mucoidy and Cell Densitymentioning
confidence: 99%
“…These NA1000 distinctive phenotypes include the mucoidy on high-sugar medium, a reduced sensitivity to phage ΦCr30 and the sedimentation properties which are exploited to physically separate swarmer and stalked cells by cell density centrifugation (127). The 26-kb prophage region encodes a number of putative ORFs predicted to be involved in polysaccharide synthesis and export (127). The presence of these genes could alter the capsular properties of C. crescentus, and as a consequence interfere with phage ΦCr30 attachment to the S-layer.…”
Section: Regulation Of Mucoidy and Cell Densitymentioning
confidence: 99%